Two possible causes of the stage of emission buildup after excitation by a nanosecond electron flux pulse; Optical Materials; Vol. 42 - Lisitsyn V. M. Viktor Mikhailovich; Lisitsyna L. A. Lyudmila Aleksandrovna; Karipbaev Z. T. Zhakyp Tleubaevich; Valiev D. T. Damir Talgatovich; Stepanov S. A. Sergey Aleksandrovich (2015, 2015)
Title screen